1998
DOI: 10.1152/ajpendo.1998.275.2.e249
|View full text |Cite
|
Sign up to set email alerts
|

Organ-tissue mass measurement allows modeling of REE and metabolically active tissue mass

Abstract: Investigators have expressed interest in the associations between resting energy expenditure (REE) and body mass for over a century. Traditionally, descriptive models using regression analysis are applied, linking REE with metabolically active compartments such as body cell mass (BCM) and fat-free body mass (FFM). Recently developed whole body magnetic resonance imaging (MRI) and echocardiography methods now allow estimation of all major organs and tissue volumes in vivo. Because measured values are available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
432
5
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 341 publications
(457 citation statements)
references
References 28 publications
13
432
5
7
Order By: Relevance
“…However, neither with the results of our investigation in which weights of the brain, heart, liver and kidneys were calculated by regression equations according to Garby et al (1993) nor with the results of Gallagher et al (2000), who measured the volumes of the organs and tissues by magnetic resonance imaging, can it be explained whether the decline in RMR independently of changes in body composition relates to a reduction in the organs' metabolic rate or whether this is due, for example, to morphological changes like infiltration of the organs with fat, oedema or cystic structures (Gallagher et al, 1998). Future studies should focus therefore on oxygen consumption of specific organs and its relation to respective anatomical, physiological or biochemical changes in these tissues associated with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neither with the results of our investigation in which weights of the brain, heart, liver and kidneys were calculated by regression equations according to Garby et al (1993) nor with the results of Gallagher et al (2000), who measured the volumes of the organs and tissues by magnetic resonance imaging, can it be explained whether the decline in RMR independently of changes in body composition relates to a reduction in the organs' metabolic rate or whether this is due, for example, to morphological changes like infiltration of the organs with fat, oedema or cystic structures (Gallagher et al, 1998). Future studies should focus therefore on oxygen consumption of specific organs and its relation to respective anatomical, physiological or biochemical changes in these tissues associated with age.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to investigate this question is to calculate RMR on the basis of individual tissue masses and their specific metabolic rates and to compare calculated RMR to RMR assessed by indirect calorimetry (Gallagher et al, 1998). Gallagher et al (2000) employed this approach of calculated and measured RMR in a small sample of seven elderly women and six elderly men.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally RMR data have to be corrected for differences in FFM (Deurenberg, 1994), although it can be argued that such a correction is only a very crude one. Gallagher et al (1998) recently showed that the FFM is not one entity in that different components of the FFM have different contributions to the RMR. Based on their data it can be argued that obese subjects will have a lower RMR per kg body mass or even per kg fat-free mass, as their organ contribution per kg body weight or per kg FFM will be relatively lower.…”
Section: Discussionmentioning
confidence: 99%
“…Total body adipose tissue volume, SM volume, and ATFM were evaluated by whole-body MRI in Asian men age Ն18 yr at the NY Obesity Research Center. Compartment volumes were converted to mass using previously reported (7,37) densities for adipose tissue (0.92 kg/l), SM (1.04 kg/l), and ATFM (1.04 kg/l). Bone mineral content (BMC) was measured by DXA on the same day and results were converted to bone mass as BMC/0.54 (12,37).…”
Section: Experimental Design and Rationalementioning
confidence: 99%
“…Since brain is a high-metabolic-rate organ (ϳ240 kcal⅐kg Ϫ1 ⅐day Ϫ1 ; Ref. 7), a relatively smaller brain mass may provide a partial mechanistic explanation for the lower REE/ body weight observed in taller men.…”
mentioning
confidence: 99%